1997
DOI: 10.1155/np.1997.73
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Dopaminergic Neurons Transplanted to the Normal Striatum of Neonatal or Adult Rats and to the Denervated Striatum of Adult Rats

Abstract: Fetal ventral mesencephalon from the 15th gestational day was grafted into the striatum of neonatal and adult rats. In one group of adult rats, fetal nigra was transplanted into normal striatum. In a second group, the tissue was transplanted at sites where dopaminergic fibers were denervated with 6-hydroxydopamine. The behavior of the dopaminergic neurons and glial reactions were studied by staining with cresyl violet to localize the transplants and by immunolabeling tyrosine hydroxylase (TH) and glial fibrill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Some hope is provided by the transplantation studies of Sun et al [38], who demonstrated enhanced survival of neural stem cells into the 6-OHDA lesioned striatum of rats and observed greater survival and more differentiation into TH-positive cells in these mice than in controls. Further evidence that the adult intact striatum is less conducive for transplantation compared to denervated striatum was demonstrated by Sable et al [37], whereas Joannides et al [23] and, as mentioned above, Sun et al [38] demonstrated that pathological conditions enhance neural formation. This may explain why the HUCB cells did not survive to 1 month in our study.…”
Section: Discussionmentioning
confidence: 92%
“…Some hope is provided by the transplantation studies of Sun et al [38], who demonstrated enhanced survival of neural stem cells into the 6-OHDA lesioned striatum of rats and observed greater survival and more differentiation into TH-positive cells in these mice than in controls. Further evidence that the adult intact striatum is less conducive for transplantation compared to denervated striatum was demonstrated by Sable et al [37], whereas Joannides et al [23] and, as mentioned above, Sun et al [38] demonstrated that pathological conditions enhance neural formation. This may explain why the HUCB cells did not survive to 1 month in our study.…”
Section: Discussionmentioning
confidence: 92%